Prayer : the chief exercise of faith : the centrality of prayer in faith and obedience according to Karl Barth - Van Zyl, Marthinus Stephanus (Stellenbosch : Stellenbosch University, 2013)
Thesis (PhD)--Stellenbosch University, 2013.